Bohémiens condamnés aux galères à l’époque du Roi-Soleil (1677 à 1715) - Emmanuel Filhol (Criminocorpus)
Despite the interest and enthusiasm shown in France in the field of entertainment arts by aristocratic groups and the Court towards Gypsies, the Declaration of 1682 due to Louis XIV and Colbert against the Bohemians condemns them to life on the galleys. Those whom the marechaussee (stops) arrests, just because they are Bohemians, follow the routes of the chains of convicts (from Paris, Rennes and Bordeaux) who (that) lead them to Marseille in order to serve on the galleys of the Sun King.